Atypical nucleoprotein complexes mediate CRE-dependent regulation of the early promoter of minute virus of mice - Perros, Manoussos; Rommelaere, Jean (Journal of general virology, 1999)
The P4 promoter of the parvovirus minute virus of mice (MVMp) directs transcription of the genes encoding non-structural proteins. We have previously shown that functional upstream CRE elements contribute to both the ras oncogene-dependent activation of promoter P4 and its down-modulation by known activators of cyclic AMP-dependent protein kinase A (PKA). In the present work, the nucleoprotein complexes formed with the P4 CRE elements were characterized with regard to their polypeptide constituents and the nucleotides taking part in the interaction. Atypical interactions, both at the protein-protein and protein-DNA level, were observed, which may be a reflection of the divergence of the parvoviral CREs from the usual consensus. The CRE-mediated regulation of promoter P4 by PKA and Ras is discussed in light of these findings.,
Gesehen am 12.02.2021